Problems Encountered In Oral Presentation Through Online Learning of The Students at English Education Department of Muhammadiyah University Of Makassar - Awalia, Dina; Firman; Maryam Hamid, Sitti (FKIP Unismuh Makassar, 2020)
Since pandemic of covid-19, the learning process transformed into online learning and become popular nowadays. This study aimed to find out the problem encountered in oral presentation through online learning of the students at English education department of Muhammadiyah University of Makassar. This research applied a descriptive qualitative research design because it aimed to exploring the students problem in doing online presentation. The subject of the research was B class at fourth semester students of English department in Muhammadiyah University of Makassar in academic years 2021/2022. The students who had obstacles in doing presentation were invited and the total subject were 10 students. The interview were conducted as the instrument of the study based on the two aspects such as linguistic problem and non-linguistic problem. The result of this study showed that students had some problem in online oral presentation both in linguistic and non-linguistic aspects. The linguistic aspects consisted of material comprehension, fluency and accuracy. Furthermore, non-linguistic problem consisted of network and psychological factor such as self-esteem, anxiety, and motivation. The researcher hoped that the results of this study could have a good impact on teachers, students and future researchers as a reference to provide progress, especially in oral presentation.